1983
DOI: 10.3171/jns.1983.59.2.0276
|View full text |Cite
|
Sign up to set email alerts
|

The National Traumatic Coma Data Bank

Abstract: This paper describes the pilot phase of the National Traumatic Coma Data Bank, a cooperative effort of six clinical head-injury centers in the United States. Data were collected on 581 hospitalized patients with severe non-penetrating traumatic head injury. Severe head injury was defined on the basis of a Glasgow Coma Scale (GCS) score of 8 or less following nonsurgical resuscitation or deterioration to a GCS score of 8 or less within 48 hours after head injury. A common data collection protocol, definitions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(19 citation statements)
references
References 2 publications
0
16
0
3
Order By: Relevance
“…[17] A single episode of hypotension was associated with increased morbidity and mortality. [17] A meta-analysis of 8721 patients (IMPACT study) also suggested that hypotension and hypoxia were significantly associated with unfavorable 6-month outcome.…”
Section: Pathophysiology Of Traumatic Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…[17] A single episode of hypotension was associated with increased morbidity and mortality. [17] A meta-analysis of 8721 patients (IMPACT study) also suggested that hypotension and hypoxia were significantly associated with unfavorable 6-month outcome.…”
Section: Pathophysiology Of Traumatic Brain Injurymentioning
confidence: 99%
“…[17] A single episode of hypotension was associated with increased morbidity and mortality. [17] A meta-analysis of 8721 patients (IMPACT study) also suggested that hypotension and hypoxia were significantly associated with unfavorable 6-month outcome. [18] A study on the association between intraoperative hypotension and outcome demonstrated that patients who had intraoperative hypotension had over three times increased mortality than normotensive patients.…”
Section: Pathophysiology Of Traumatic Brain Injurymentioning
confidence: 99%
“…Marshall et al [6] have used this strategy. The investigators call it ‘pseudoscoring’ probably because the true verbal score in some of these patients may be more than ‘1’, but aphasia or intubation limits the determination of the true score.…”
Section: Methodsmentioning
confidence: 99%
“…Other reports have also encountered the problem in scoring the verbal subscale [4, 5]. Investigators have employed three different strategies to deal with this problem in patients with untestable verbal subscale: some have used a pseudoscore of ‘1’ for the verbal subscale [6] while others have completely eliminated the verbal subscale and used only the eye and motor subscale (short form) of the GCS [5, 7] or have substituted the verbal score of such patients with the median verbal score of patients with the same eye and motor scores but with lesions of the nondominant hemisphere [8]. There is little discussion in the literature on the relative merits and demerits of the three strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral CT scan was carried out at admission and after 48 h. The CT scan findings were evaluated using a modification of the Traumatic Coma Data Bank CT scan classification system [6]. …”
Section: Methodsmentioning
confidence: 99%